Antimicrobial resistance and virulence factors analysis of a multidrug-resistant Acinetobacter baumannii isolated from chickens using whole-genome sequencing - Lumin Yu; Yuzhong Zhao; Shanpeng Zhang; Weishi Ni; Lingling Zhang; Cong Xue; Peikun Wang; Xinglin Zhang (BMC Microbiology)
Abstract Multidrug-resistant (MDR) Acinetobacter baumannii (A. baumannii) is currently recognized not only as a significant nosocomial pathogen but also is an emerging bacterial infection in food-producing animals, posing a critical threat to global health. However, this is a hindrance to detailed bioinformatic studies of MDR A. baumannii of chicken origin due to the lack of its complete genome sequence. Here, we report whole-genome sequencing analysis of MDR A. baumannii Y03 isolated from chickens. The Y03 genome consists of 1 circular chromosome and 4 circular plasmids, The Y03 chromosome harbors 41 antimicrobial resistance genes conferring resistance to major classes of antibiotics, including β-lactams, phenicols, macrolides, lincosamides, aminoglycosides, and nitrofurans, as well as 135 virulence factors involved in effector delivery system, immune modulation, adherence, stress survival, biofilm, exotoxin, and nutritional/metabolic factor. The in vivo infection experiments certificated that Y03 was virulent to chickens. Meanwhile, we used PCR amplification method to detect 10 antimicrobial resistance genes including abeM, adeB, adeH, adeK, bla apmC , bla OXA−90 , catB9, macB, folP, and parE, as well as 14 virulence genes including lpxC, pilO, fimT, ompA, basA, bauA, gspL, csu, pgaC, plc2, tssA, tviB, bap, and vgrG. Whole-genome sequencing analysis revealed that Y03 contained 46 horizontal gene transfer elements, including 11 genomic islands, 30 transposons, and 5 prophages, as well as 518 mutations associated with reduced virulence and 44 mutations resulting in loss of pathogenicity. Furthermore, there were 22 antibiotic targets and 28 lethal mutations on the Y03 chromosome that could be used as potential targets to prevent, control, and treat infections caused by MDR A. baumannii Y03. Therefore, this study contributes to the development of strategies for the prevention, control, and treatment of A. baumannii infections and their spread in chickens.